1997
DOI: 10.1111/j.1439-037x.1997.tb00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Relative Sowing Time on the Growth and Yield of the Component Crops in Okra/Maize and Okra/Cowpea Intercropping Systems

Abstract: The effects of variations in the relative sowing time of component crops in okra/maize and okra/cowpea intercropping systems were examined in 1990 and 1991 cropping seasons. Okra was either sown the same day as, or two weeks before or after maize or cowpea. Intercropping reduced the growth and yield of okra, maize and cowpea relative to their sole crops. However, okra yield was depressed more by maize than by cowpea, especially when okra was sown two weeks after maize. Comparative assessment of okra/maize and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
5
5
0
Order By: Relevance
“…as compared with the pure stands and the other treatments in both seasons. Similar results were obtained by Dahmardeh et al (2010), Adeniyan et al (2011), Akbar et al (2012, Ewansiha et al (2015), Mahdy and El-Said (2015), Moriri et al (2015), Muoneke et al (2015) and Mahdy and El-Said (2017).…”
Section: The Effect On Cow Peasupporting
confidence: 80%
“…as compared with the pure stands and the other treatments in both seasons. Similar results were obtained by Dahmardeh et al (2010), Adeniyan et al (2011), Akbar et al (2012, Ewansiha et al (2015), Mahdy and El-Said (2015), Moriri et al (2015), Muoneke et al (2015) and Mahdy and El-Said (2017).…”
Section: The Effect On Cow Peasupporting
confidence: 80%
“…The highest yield advantage for the two cropping season of 2.6 was obtained by intercropping Nhae 47-4 with Tis 2532.op.1.13 sweet potato or Tae 38 okra with Tis 87/0087 sweet potato. This confirms similar result obtained by Muoneke and Asiegbu (1997) in okra cowpea mixture. The superior LER obtained by the intercropping made the mixture a more productive option and agree with earlier reports of Pinchinat, et al (1976) who had recommended crop mixtures yielding LER of 1.39 to 1.63 as being good mixtures.…”
Section: The Total Land Equivalent Ratio (Ler) For 2000 and 2001supporting
confidence: 92%
“…The generally more leaf production obtained for intercropped plots compared to the control at the different manure rates (0, 5, 10 and 20 t/ha) showed the effect of etiolation where plants in the bid to catch sunlight exert greater growth vigour compared to those in control plots that were not intercropped. Earlier reports by [63] and [64] had reported that intercropped okra was…”
mentioning
confidence: 99%